Acute Pyogenic Osteomyelitis of the Pubic Bone in a Patient with Systemic Lupus Erythematosus Mimicking Fracture of the Pubic Bone and Periprosthetic Joint Infection of the Hip - Aysha Rajeev; Jason Mavrotas; Sanjay Taribagil; Jonathan Loughead (Case Reports in Orthopedics)
Introduction. Pubic bone osteomyelitis is atypical, and the diagnosis is often overlooked. It may present as osteitis pubis, fracture, or noninfectious inflammation of the pubic symphysis. Case Report. We report a case of a 65-year-old lady who has systemic lupus erythematosus with acute pyogenic osteomyelitis of the pubic bone who presented initially with a suspicious healing pubic rami fracture and periprosthetic infection of the hip joint. Conclusion. Acute osteomyelitis of the pubic bone has often an infrequent and delayed presentation. Clinical awareness, early diagnosis, and appropriate treatment including surgical debridement and long-term antibiotics can prevent ongoing morbidities such as chronic osteomyelitis, pain, and deformities of pelvic bone and joints.